Perubahan perilaku ibu hamil tentang hiv/aids (metode:pre-post konseling personal) - Hasnia; Pratami, Yustika Rahmawati; Vitania, Wiwit; Handayani, Endah Purwanti; Astutik, Eftyaningrum Dwi Wahyu; Nasrianti (STIKES Bethesda Yakkum, 2024)
Pregnancy and the postpartum period are periods with a continuous and ongoing risk of being infected with HIV/AIDS. Pregnant and breastfeeding women (postpartum period) living with HIV are targets for mother-to-child HIV prevention. HIV transmission generally occurs as a result of human behavior, thereby placing individuals in a situation that is vulnerable to infection. HIV infection is a group of infectious diseases and is one of the factors that can influence maternal and child mortality. This research aims to analyze the behavior of pregnant women regarding HIV/AIDS using pre and post personal counseling methods at the Sentani Community Health Center, Jayapura Regency in 2024. The research sample is pregnant women using a purposive sampling technique according to predetermined criteria. Data analysis used a non-parametric test, namely the Mc Nemar test. The results obtained were changes in pregnant women's knowledge about HIV/AIDS with the results of calculating 05, there was a change in the attitude of pregnant women regarding HIV/AIDS prevention obtained by X2 count 25.03 > 3.841 value α= 0.031 < 0.05. There was a change in the behavior of pregnant women towards preventing HIV/AIDS, obtained X2 count 6.32 > 3.841 value α= 0.500 < 0.05. From these results, it can be concluded that there has been a change in the knowledge, attitudes and behavior of pregnant women regarding HIV/AIDS prevention at the Sentani Community Health Center, Jayapura Regency. It is recommended that pregnant women be more active in seeking information independently about HIV/AIDS and for health workers to continue to increase their knowledge about HIV/AIDS so that they can distribute appropriate and quality information to pregnant women.